2009
DOI: 10.1111/j.1464-5491.2009.02720.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypical aspects of maturity‐onset diabetes of the young (MODY diabetes) in comparison with Type 2 diabetes mellitus (T2DM) in children and adolescents: experience from a large multicentre database

Abstract: The prevalence of MODY in children and adolescents in Germany and Austria is lower than that of T2DM in this age group. Dyslipidaemia and hypertension are less frequent in MODY compared with T2DM patients, but do occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
1
15

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(134 citation statements)
references
References 36 publications
9
109
1
15
Order By: Relevance
“…This difference only nearly attained statistical significance, but supports the fact that mutations found in the transactivation domain were mostly nonsense or frameshift as well as the possibility that these patients may have had more severe clinical phenotypes, requiring insulin more often. Others studies also found a fairly high proportion of patients with more severe clinical phenotypes resulting from HNF1A mutations to use insulin treatment and that with disease progression, (15,16). Mutation isoform and domain of occurrence associated with age at disease onset in certain studies examining larger numbers and older subjects.…”
Section: Discussionmentioning
confidence: 99%
“…This difference only nearly attained statistical significance, but supports the fact that mutations found in the transactivation domain were mostly nonsense or frameshift as well as the possibility that these patients may have had more severe clinical phenotypes, requiring insulin more often. Others studies also found a fairly high proportion of patients with more severe clinical phenotypes resulting from HNF1A mutations to use insulin treatment and that with disease progression, (15,16). Mutation isoform and domain of occurrence associated with age at disease onset in certain studies examining larger numbers and older subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of GCK-MODY in Children and Adults With Incidental Hyperglycemia GCK-MODY is a very common cause (23-65%) of incidental hyperglycemia in children, especially when the fasting glucose is persistently above 5.5 mmol/L (29,(40)(41)(42)(43)(44). Awareness of such high GCK-MODY prevalence rates in children with mild fasting hyperglycemia will aid early, correct diagnosis and management.…”
Section: Prevalence Of Gck-mody In Modymentioning
confidence: 99%
“…Maturity-onset of diabetes mellitus of the young (MODY) is another rare form of diabetes mellitus in children that includes several disorders caused by monogenic defects in β-cell function [44] . MODY 2 (defect in glucokinase) and MODY 3 (defect in HNF1α) are the most frequent types of MODY.…”
Section: Differential Diagnosis Of Type 2 Diabetes Mellitus In Childrmentioning
confidence: 99%